Embolism resistance supports the contribution of dry-season precipitation to transpiration in eastern Amazon forests - Magali F. Nehemy; Caio R. C. Mattos; Rafael S. Oliveira; Marina Hirota; Ying Fan; Monique B. Schlickmann; Deliane Penha; Leandro L. Giacomin; Julliene S. G. M. Silva; Mayda Rocha; Gleicy A. Rodrigues; Jeffrey J. McDonnell (Proceedings of the National Academy of Sciences, 2025)
Transpiration drives most of the local rainfall during the dry season in the Amazon forests by recycling moisture into the atmosphere. However, the source, temporal origin of transpiration, and spatial distribution of transpiration water sources remain unclear. Here, we quantify transpiration sources across a topographic gradient in the eastern Amazon. We show that on hills, dry-season transpiration sources are mostly shallow soil water recharged by dry-season rainfall. This is different in valleys, where tree water sources include both shallow and deep soil layers, with both dry- and wet-season contributions. We show that species embolism resistance largely explains this pattern in tree water use but with contrasting trade-offs between topographic positions. The significant relationship between embolism resistance and depth of water uptake in both hill and valley species may merit incorporation into process-based models to understand changes in vegetation and land surface fluxes.